Silver plating material, terminal for electric contact, and production method of silver plating material

JP2025026366AActive Publication Date: 2025-02-21DOWA METALTECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024124340
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-09
Filing Date
2024-07-31
Publication Date
2025-02-21
Estimated Expiration
2044-07-31

AI Technical Summary

Benefits of technology

【0020】 本発明によれば、銀めっき層において初期状態での硬度および100℃での耐熱性を有するとともに光沢度を向上させることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025026366000001
    Figure 2025026366000001
  • Figure 2025026366000002
    Figure 2025026366000002
Patent Text Reader

Abstract

To improve hardness in an initial state, heat resistance at 100°C, and glossiness in a silver plating layer.SOLUTION: A silver plating material has a silver plating layer on a substrate. The surface of the base material is copper or a copper alloy, and the silver plating layer comprises selenium. The silver plating material has a Vickers hardness in an initial state and a Vickers hardness after heating at 100°C for 168 hours, both of which are 120 HV or more. The glossiness of the silver plating layer is 1.0 or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a silver-plated product, a terminal for electrical contacts, and a method for producing the silver-plated product. [Background technology]

[0002] 2. Description of the Related Art Conventionally, as materials for contacts and terminal parts of connectors, switches and the like, plated materials have been used in which a base material that is relatively inexpensive and has excellent corrosion resistance and mechanical properties, such as copper, copper alloys, or stainless steel, is plated with tin, silver, gold, or the like depending on the required properties, such as electrical properties and solderability.

[0003] Tin-plated products, which are made by plating tin on a substrate such as copper or copper alloy or stainless steel, are inexpensive but have poor corrosion resistance in high-temperature environments. Gold-plated products, which are made by plating gold on these substrates, have excellent corrosion resistance and high reliability, but are expensive. On the other hand, silver-plated products, which are made by plating Ag (silver) on these substrates, are inexpensive compared to gold-plated products and have excellent corrosion resistance compared to tin-plated products.

[0004] However, because silver-plated materials are soft and easily worn, when used as materials for connection terminals and the like, there are problems in that adhesion wear occurs easily due to adhesion caused by insertion / removal and sliding, and that the surface is scraped off when the connection terminal is inserted, increasing the coefficient of friction and resulting in a high insertion force.

[0005] In order to solve such problems, a technique has been proposed in which the hardness of a silver-plated product is improved by incorporating elements such as selenium (Se) into the silver plating (see, for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Republished WO2018 / 181190 [Patent Document 2] JP 2015-110833 A Summary of the Invention [Problem to be solved by the invention]

[0007] The silver-plated products of Patent Documents 1 and 2 described above have excellent hardness due to the inclusion of selenium. The plated product of Patent Document 2 uses a silver plating solution containing 70 mg / L or less of selenium, and has a predetermined hardness before a heat resistance test, and is able to maintain the predetermined hardness even after the heat resistance test in which the product is heated at 50°C for a predetermined time. The heat resistance of the plated product refers to the heat resistance of the hardness of the plated product.

[0008] In recent years, there has been a demand for improved heat resistance in plated materials for automobiles and other vehicles that are used outdoors for long periods of time, such as high-voltage terminals for electric vehicles such as EVs and HEVs. They are required to be able to maintain a certain level of hardness even when heated for a certain period of time at a temperature higher than 50°C, for example, 100°C. In this regard, the silver-plated material of the above-mentioned Patent Document 2 was sometimes unable to maintain a high level of hardness when heated to 100°C.

[0009] Generally, silver-plated products are also required to have a high degree of gloss from the standpoint of appearance.

[0010] An object of the present invention is to provide a silver-plated product having a silver-plated layer with high initial hardness, heat resistance at 100° C., and high gloss, and a manufacturing technique therefor. [Means for solving the problem]

[0011] The present inventors have formed a silver-plated product by significantly increasing the selenium concentration in the silver plating bath so as to increase the selenium content in the silver-plated product, and have found that the heat resistance of the silver-plated product at high temperatures tends to improve, but the surface of the plating layer becomes rough, the plating layer becomes white, and the glossiness decreases. Therefore, the present inventors have investigated a method for suppressing the surface roughness and whitening caused by selenium while increasing the selenium concentration in the silver plating bath. As a result, they have found that it is effective to add a sulfonic acid group-containing polymer to the silver plating bath in which the silver plating layer is formed. As shown in the examples described later, when the silver plating layer is formed in the presence of these additives, the surface roughness of the silver plating layer can be reduced and whitening can be suppressed, and a high glossiness can be achieved, even while increasing the selenium concentration in the silver plating bath to a specific range.

[0012] The aspects of the present invention created based on the above findings are as follows.

[0013] The first aspect of the present invention is A silver-plated product having a silver plating layer on a substrate, the surface of the substrate is copper or a copper alloy; The silver plating layer contains selenium, the Vickers hardness in the initial state and the Vickers hardness after heating at 100°C for 168 hours are both 120 HV or more, and the gloss of the silver plating layer is 1.0 or more; Silver plated material.

[0014] The second aspect of the present invention is the method according to the first aspect, The ratio of the Vickers hardness after heating to the Vickers hardness in the initial state is 95% or more.

[0015] A third aspect of the present invention is the method according to the first or second aspect, The preferred orientation plane of the silver plating layer in the initial state is the {111} plane.

[0016] A fourth aspect of the present invention is the method according to any one of the first to third aspects, A nickel-containing underlayer is provided between the substrate and the silver plating layer.

[0017] A fifth aspect of the present invention is A terminal for electrical contacts, which is made of the silver-plated product according to any one of the first to fourth aspects.

[0018] A sixth aspect of the present invention is a method for producing a composition comprising the steps of: The method includes a step of forming a silver plating layer on a substrate having a copper or copper alloy surface, In the step of forming the silver plating layer, a silver plating bath is used that contains silver cyanide or silver potassium cyanide, a cyanide salt, a selenium compound, and a sulfonic acid group-containing polymer, and the ratio of the concentration of selenium derived from the selenium compound to the concentration of the cyanide salt is more than 0.1%. A manufacturing method for silver-plated products.

[0019] A seventh aspect of the present invention relates to the sixth aspect, The selenium concentration derived from the selenium compound is 85 mg / L or more and 200 mg / L or less. Effect of the Invention

[0020] According to the present invention, it is possible to provide a silver plating layer with initial hardness and heat resistance at 100° C., and to improve the gloss. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The present embodiment will be described below. In this specification, the initial state refers to the state within several days immediately after the silver-plated product is formed and before it is heated for evaluating heat resistance. In this specification, "to" refers to a value greater than or equal to a specified value and less than or equal to a specified value.

[0022] (1) Silver plating bath First, a silver plating bath for forming the silver plating layer of a silver-plated product will be described.

[0023] The silver plating bath of this embodiment contains silver cyanide or potassium silver cyanide, a cyanide salt, a selenium compound, and a sulfonic acid group-containing polymer.

[0024] Silver cyanide or potassium silver cyanide can be used to supply silver in the silver plating bath. Commercially available silver cyanide or potassium silver cyanide can be used. Among them, it is preferable to use potassium silver cyanide. The concentration of silver cyanide or potassium silver cyanide in the silver plating bath is not particularly limited as long as a silver plating layer can be formed, but if the silver concentration is too low, the film formation speed will be slow, and if it is too high, the consumption of silver due to the take-out of the plating solution will increase, which is uneconomical. From the viewpoint of the formation speed of the silver plating layer and cost reduction, for example, the concentration of silver cyanide or potassium silver cyanide may be adjusted so that the silver concentration in the silver plating bath is 40 to 110 g / L. For example, in the case of potassium silver cyanide, the concentration may be 74 to 203 g / L.

[0025] As the cyanide salt, a known component can be used, for example, potassium cyanide, sodium cyanide, etc. can be used. Among them, potassium cyanide is preferably used. The concentration of the cyanide salt is preferably set according to the selenium concentration so that the selenium concentration derived from the selenium compound described later is in a range exceeding 0.1% relative to the concentration of the cyanide salt. For example, from the viewpoint of favorably forming a silver plating layer, the concentration of the cyanide salt is preferably 70 to 160 g / L, more preferably 75 to 125 g / L. If the concentration of the cyanide salt is less than 70 g / L, the current efficiency of the anode may decrease and the silver of the anode may become difficult to dissolve. On the other hand, if the concentration of the cyanide salt exceeds 160 g / L, the selenium concentration may become excessively high by adjusting the selenium concentration to exceed 0.1% relative to the concentration of the cyanide salt, so that the surface of the silver plating layer may become rough and whitening may occur. The concentration of the cyanide salt corresponds to the amount of the cyanide salt added to the silver plating bath.

[0026] As the selenium compound, a known additive for adding selenium to a cyanide-based silver plating bath can be used, such as potassium selenocyanate, potassium selenate, selenium dioxide, etc. The selenium compound is a component that acts to improve the hardness and heat resistance of the silver plating layer.

[0027] From the viewpoint of realizing the hardness in the initial state and the heat resistance at 100°C in the silver plating layer described later, the concentration of the selenium compound is in a range such that the selenium concentration derived from the selenium compound exceeds 0.1% relative to the concentration of the cyanide salt. The ratio of the selenium concentration derived from the selenium compound in g / L to the concentration of the cyanide salt in g / L is preferably 0.11% or more and 0.3% or less, and the ratio of the selenium concentration derived from the selenium compound to the concentration of the cyanide salt is more preferably 0.2% or less. Here, the selenium concentration derived from the selenium compound (hereinafter also simply referred to as selenium concentration) is a value calculated by multiplying the concentration of the selenium compound divided by its molecular weight by the atomic weight of selenium. If the ratio is 0.1% or less, the silver plating layer may have low heat resistance at 100°C, and if it exceeds 0.3%, there is a risk that the decrease in gloss cannot be suppressed. By adjusting the selenium concentration to a predetermined ratio relative to the cyanide salt concentration and adding a sulfonic acid group-containing polymer described below, it is possible to obtain a high gloss, improve the initial hardness, and improve heat resistance at 100°C.

[0028] The selenium concentration in the silver plating bath is preferably 85 mg / L or more and 300 mg / L or less, more preferably 85 mg / L or more and 200 mg / L or less, and more preferably 100 mg / L or more and 200 mg / L or less. For example, when potassium selenocyanate is used as the selenium compound, the concentration of potassium selenocyanate is preferably 155 mg / L or more and 548 mg / L or less from the viewpoint of realizing the above selenium concentration in the silver plating bath. If the selenium concentration is less than 85 mg / L, the heat resistance of the silver plating layer at 100°C may be reduced. On the other hand, if the selenium concentration exceeds 300 mg / L, the gloss of the silver plating layer may be reduced and whitening may occur even if a sulfonic acid group-containing polymer is used.

[0029] The sulfonic acid group-containing polymer is a compound that acts to suppress surface roughening caused by selenium and improve the glossiness of a silver plating layer when the layer is formed. The sulfonic acid group-containing polymer is preferably an aromatic sulfonic acid polymer. As the aromatic sulfonic acid polymer, a naphthalene sulfonate formaldehyde condensate or sodium polystyrene sulfonate can be suitably used, and for example, a sodium salt of β-naphthalene sulfonate formalin condensate (for example, "Demol N (registered trademark)" manufactured by Kao Corporation) can be used.

[0030] The concentration of the sulfonic acid group-containing polymer is not particularly limited, but from the viewpoint of suppressing surface roughness of the silver plating layer and improving the gloss, the concentration of the sulfonic acid group-containing polymer is preferably 0.1 g / L or more and 10 g / L or less.

[0031] The silver plating bath may contain other additives in addition to the above components. Examples of the other additives include conventionally known components such as hardeners such as carbon sulfide compounds (such as carbon disulfide) and inorganic sulfur compounds (such as sodium thiosulfate), and conductive salts such as potassium carbonate.

[0032] In addition, when the other additives contain antimony as a component, it is preferable that the antimony concentration is lower than the selenium concentration in the silver plating bath, and more preferably, no antimony compound is contained as the other additives.

[0033] The silver plating bath also contains a solvent. As the solvent, water is preferred because of its ability to dissolve other components contained in the silver plating bath and its low environmental impact. As the solvent, water is preferably used, and a mixed solvent of water and alcohol may also be used.

[0034] (2) Manufacturing method of silver-plated products Next, a method for manufacturing a silver-plated product according to the present embodiment will be described. The method for manufacturing a silver-plated product includes a step of forming a silver-plated layer on a substrate whose surface is copper or a copper alloy. Before the step of forming the silver-plated layer, a step of forming another layer on the substrate may be performed. Below, a silver-plated product in which an undercoat layer, a strike-plated layer, and a silver plating are formed on the substrate in this order will be described, but the undercoat layer and the strike-plated layer may not be formed, and may be formed as necessary.

[0035] (preparation process) First, a substrate to be plated is prepared.

[0036] The material of the substrate is preferably one that can be silver plated and has the conductivity required for materials such as sliding electrical contact parts such as switches and connectors. The surface of the substrate to be silver plated is copper or a copper alloy. The material other than the surface is selected according to the application. The entire substrate may be copper or a copper alloy. As the material of the substrate surface, pure copper can be used, for example, and the purity of pure copper can be 3N to 5N. As the copper alloy, from the viewpoint of conductivity and strength, an alloy composed of Cu, at least one selected from the group consisting of Si (silicon), Fe (iron), Mg (magnesium), P (phosphorus), Ni (nickel), Sn (tin), Co (cobalt), Zn (zinc), Be (beryllium), Pb (lead), Te (tellurium), Ag (silver), Zr (zirconium), Cr (chromium), Al (aluminum) and Ti (titanium), and inevitable impurities is preferable. Brass or bronze may also be used. The amount of Cu in the copper alloy may be 60 mass% or more.

[0037] As described below, the substrate is preferably used for terminal applications (as a silver-plated material on which a silver plating layer is formed), but the substrate itself may have a shape for such applications, or the substrate may have a flat shape (such as a flat plate shape) and be formed into the shape for application after becoming a silver-plated material.

[0038] (Underlying layer formation process) If necessary, a base layer may be formed on the substrate before the formation of the silver plating layer. The base layer can prevent the components of the substrate, such as copper, from diffusing to the plating surface and oxidizing, thereby causing a deterioration in the electrical conductivity of the silver-plated product, and can improve the adhesion of the silver plating layer.

[0039] The constituent metal of the underlayer may be at least one metal or alloy selected from the group consisting of Cu, Ni, Sn, and Ag. For example, when the substrate is made of copper and copper in the substrate is to be prevented from diffusing to the surface of the silver plating layer to deteriorate the electrical conductivity, it is preferable to form an underlayer containing Ni. For example, when the substrate is made of a copper alloy containing zinc such as brass and zinc in the substrate is to be prevented from diffusing to the surface of the silver plating layer, it is preferable to form an underlayer containing Cu. For example, when the adhesion of the silver plating layer to the substrate is to be improved, it is preferable to form an underlayer containing Ag.

[0040] The underlayer may be a single layer made of Cu, Ni, Sn, Ag or an alloy thereof, or a layer made of a combination of these (a laminate structure). The underlayer may be formed on the entire surface of the base material or only on a part of it, depending on the application of the silver-plated product to be manufactured.

[0041] The thickness of the underlayer is not particularly limited, but from the viewpoints of functionality and cost, it is preferably 0.1 to 2 μm, and more preferably 0.2 to 1.5 μm.

[0042] The method for forming the underlayer is not particularly limited, and it can be formed by electroplating using a plating bath containing ions of the above-mentioned constituent metals using a known method, or by stacking layers made of each metal that constitutes the desired alloy layer in order and then reflowing (heat treating).

[0043] (Strike plating process) A strike plating layer may be formed on the substrate or the above-mentioned underlayer. The strike plating layer can enhance the adhesion between the substrate and the silver plating layer. The strike plating layer can be formed by a conventional method, for example, Ag strike plating. The thickness of the strike plating layer may be thinner than other layers, for example, 5 nm or more.

[0044] (Silver plating layer formation process) Next, a silver plating layer is formed on the substrate (for example, on the strike plating layer) using the silver plating bath described above.

[0045] Specifically, a cathode and an anode are first immersed in a silver plating bath and silver plating is performed by passing an electric current through the cathode, which is the substrate to be plated, and a silver electrode plate that dissolves to provide silver ions, for example, is the anode.

[0046] In this embodiment, since the silver plating bath contains a predetermined concentration of selenium, the silver plating layer can be formed to contain selenium. At this time, as described later, the silver plating layer has a predetermined hardness in the initial state and heat resistance at 100°C. Furthermore, as the value of the selenium concentration relative to the concentration of the cyanide salt in the silver plating bath increases, surface roughness tends to occur and the glossiness tends to decrease. However, by adding a sulfonic acid group-containing polymer to the silver plating bath and performing silver plating in the presence of the polymer, surface roughness can be suppressed and the glossiness can be maintained high.

[0047] In addition, it is preferable to use the above-mentioned silver plating bath to form a silver plating layer having a predetermined hardness and a preferred orientation plane on the surface of the silver plating layer being the {111} plane. By forming the silver plating layer in this manner, it is possible to suppress an increase in contact resistance while having a high hardness. Here, the preferred orientation plane is evaluated in the above-mentioned initial state.

[0048] The plating conditions for forming the silver plating layer include, for example, the current density, plating temperature, stirring speed, plating time, etc., and each of these may be adjusted as follows.

[0049] The current density for silver plating is 0.5 to 10 A / dm from the viewpoint of the speed of formation of the silver plating layer and the suppression of unevenness in the appearance of the silver plating layer. 2 is preferable, and 1 to 10 A / dm 2 More preferably, 3 to 8 A / dm 2 is more preferred.

[0050] The temperature of the silver plating bath (plating temperature) is preferably 15 to 50°C, and more preferably 20 to 45°C, from the viewpoints of plating production efficiency and preventing excessive evaporation of the solution.

[0051] The stirring speed of the silver plating bath with a stirrer or stirring blade is preferably 300 to 700 rpm, and more preferably 350 to 650 rpm, from the viewpoint of achieving uniform plating.

[0052] The silver plating time (time for applying electric current) can be adjusted appropriately depending on the desired thickness of the silver plating layer, but is typically in the range of 25 to 1800 seconds.

[0053] The area to be plated may be the entire surface of the base material or a part of the surface of the base material, depending on the application of the silver-plated product to be manufactured.

[0054] In this manner, a silver-plated product is obtained.

[0055] (3) Silver-plated materials Next, a silver-plated product obtained by the above-mentioned method for producing a silver-plated product will be described.

[0056] The silver-plated product of this embodiment is a silver-plated product having a silver plating layer on a substrate. The silver-plated product may have a configuration including at least one of an undercoat layer and a strike plating layer between the surface of the substrate and the silver plating layer, and is also preferably a member having an undercoat layer, a strike plating layer, and a silver plating layer in this order on the surface of the substrate.

[0057] As described above, the surface of the substrate to be plated is made of copper or a copper alloy. The materials of the substrate other than the surface are selected depending on the application. The entire substrate may be made of copper or a copper alloy.

[0058] The underlayer is formed as necessary, and as described above, is formed on the surface of the base material by, for example, electroplating, and is configured to contain at least one metal or alloy selected from the group consisting of Cu, Ni, Sn, and Ag. It is preferable to use Ni for the underlayer.

[0059] As described above, the strike plating layer is formed by, for example, Ag strike plating before forming the silver plating layer. The strike plating layer may be formed thinly and integrated with the silver plating layer formed thereon. In other words, the strike plating layer may be indistinguishable from the silver plating layer.

[0060] The silver plating layer of this embodiment is formed using the above-mentioned silver plating bath. The silver plating layer may be laminated on the surface of the substrate via an undercoat layer or a strike plating layer. The silver plating layer may be formed on the entire surface of the substrate, or may be formed on a part of the surface.

[0061] The silver plating layer is formed using the silver plating bath of the present invention. As a result, the silver-plated product has a predetermined hardness in the initial state and heat resistance at 100° C. Moreover, since the silver plating layer is formed by precipitating silver in the presence of the sulfonic acid group-containing polymer using a silver plating bath containing the sulfonic acid group-containing polymer, the silver plating layer is configured to have high gloss while containing a relatively large amount of selenium and suppressing surface roughness.

[0062] Specifically, the silver-plated product has a Vickers hardness of 120 HV or more in the initial state described above. In addition, the silver-plated product has a Vickers hardness of 120 HV or more after heating at 100°C for 168 hours. In other words, the silver-plated product has a Vickers hardness of 120 HV or more both before and after heating, maintains a predetermined hardness even after heating at 100°C, and has high heat resistance at 100°C. Here, the Vickers hardness is a value measured using a hardness meter as described later in the examples.

[0063] In addition, it is preferable that the silver-plated product has high heat resistance at 100°C and the rate of change in hardness before and after heating is suppressed to a low level. Specifically, it is preferable that the ratio of the Vickers hardness after heating to the Vickers hardness in the initial state is high, for example, 95% or more. This makes it possible for the silver-plated product to maintain high hardness and desired wear resistance without being easily affected even under harsh environmental temperatures.

[0064] The silver plating layer has a glossiness of 1.0 or more. The glossiness here is a value measured using a densitometer as described later in the Examples. The glossiness tends to decrease as the surface of the silver plating layer becomes rough and whitened, and in this embodiment, the surface roughness and the resulting whitening are suppressed, so that the glossiness of the silver plating layer is 1.0 or more. The glossiness is a value in the initial state of the silver plating layer.

[0065] In addition, it is preferable that the silver plating layer has a predetermined hardness and is configured so that the preferred orientation plane in its initial state is the {111} plane. If the preferred orientation plane of the silver plating layer is, for example, the {200} plane, the hardness of the silver plating layer may become unstable due to heating or the passage of time, and if the preferred orientation plane is the {220} plane, the hardness or gloss of the silver plating layer may decrease. In this regard, by making the preferred orientation plane the {111} plane, it is possible to realize high hardness, heat resistance, and high gloss for the silver-plated material. In this embodiment, as shown in the examples described later, a sulfonic acid group-containing polymer is added to the silver plating bath and silver plating is performed in the presence of the polymer, thereby stably orienting the silver plating layer in the {111} plane.

[0066] The thickness of the silver plating layer is not particularly limited, but is preferably the minimum thickness in terms of wear resistance, reliability, and conductivity. If the silver plating layer is too thick, the effect of the silver plating layer becomes saturated and the raw material cost increases. From the above viewpoints, the thickness of the silver plating layer is preferably 0.1 μm to 45 μm, more preferably 0.5 μm to 35 μm, and even more preferably 1.5 μm to 25 μm. The thickness of the silver plating layer can be measured with a fluorescent X-ray film thickness meter, and details of the measurement method will be given in the section of Examples.

[0067] (4) Terminal The silver-plated product according to this embodiment is suitable as a constituent material for terminals for electrical contacts, particularly terminals in electrical contact parts such as switches and connectors that undergo sliding during use. EXAMPLES

[0068] EXAMPLES Hereinafter, examples of the silver-plated product and the manufacturing method thereof according to the present invention will be described in detail.

[0069] (1) Preparation of silver-plated material First, a pure copper metal substrate (purity 99.96% or more) measuring 67mm x 50mm x 0.3mm was prepared as the material to be plated (base material), and this material to be plated and a SUS plate were placed in an alkaline degreasing solution, and electrolytic degreasing was performed for 30 seconds at a voltage of 5V, with the material to be plated as the cathode and another SUS plate as the anode, and pickling was performed for 15 seconds in 3% sulfuric acid. Note that 15 seconds of water rinsing was performed between each operation.

[0070] Next, in a nickel plating solution consisting of pure water, 540 g / L of nickel sulfamate tetrahydrate, 25 g / L of nickel chloride, and 35 g / L of boric acid, the workpiece was set as the cathode and the SK nickel electrode plate as the anode, and the plating was conducted at a current density of 7 A / dm while stirring at 500 rpm with a magnetic stirrer. 2 Electroplating was performed at a solution temperature of 50° C. until the nickel film thickness reached 1 μm, forming a nickel underlayer on the substrate.

[0071] Next, in a strike silver plating solution consisting of pure water, 3 g / L of potassium cyanide silver, and 90 g / L of potassium cyanide, the workpiece was used as the cathode and a platinum-coated titanium electrode plate as the anode, and the plating was conducted at a current density of 2 A / dm while stirring at 500 rpm with a stirrer. 2 Electroplating was carried out at a temperature of 400° C. for 10 seconds to form a strike plating layer made of silver having a thickness of 0.01 μm on the underlayer.

[0072] Next, potassium silver cyanide was added to pure water, and potassium cyanide was added as a cyanide salt, potassium selenocyanate was added as a selenium compound, and "Demol N" (manufactured by Kao Corporation, sodium salt of β-naphthalenesulfonic acid formalin condensate) or sodium polystyrene sulfonate (hereinafter, simply referred to as PSS) was added as an aromatic sulfonic acid polymer, which is a type of sulfonic acid group-containing polymer, and the concentrations were appropriately changed as shown in Tables 1 and 2 below to prepare a silver plating bath. Using this silver plating bath, the plated material was used as the cathode and a silver electrode plate with a purity of 99.99% or more was used as the anode, and while stirring at 500 rpm with a stirrer, electroplating was performed on the strike plating layer at the current density and liquid temperature of the silver plating bath shown in Tables 1 and 2 below until the film thickness of the silver plating layer reached 5 μm. After silver plating, the material was washed with water for 15 seconds and dried with an air gun to obtain silver-plated materials of this example and comparative example.

[0073] The thickness of the silver plating layer was measured at the center of the sample using a fluorescent X-ray thickness gauge (FT-110A manufactured by Hitachi High-Tech Science Corporation) with a collimator diameter of φ0.2 mm and a measurement time of 10 seconds, and the measured value was recorded as the thickness. When the thickness was measured, it was confirmed that all the thicknesses were 5 μm.

[0074] In addition, in Tables 1 and 2, the Ag concentration is the silver concentration (i.e., the silver concentration derived from the concentration of potassium silver cyanide) calculated by converting the concentration of potassium silver cyanide added into silver using its molecular weight and the atomic weight of silver. The KCN concentration is the concentration of potassium cyanide added. The Se concentration is the selenium concentration (i.e., the selenium concentration derived from the concentration of potassium selenocyanate) calculated by dividing the concentration of potassium selenocyanate added by its molecular weight and multiplying it by the atomic weight of selenium. In addition, Se / KCN is the ratio of the selenium concentration converted from mg / L to g / L to the potassium cyanide concentration, whose unit is g / L. These are shown in Tables 1 and 2, respectively.

[0075] [Table 1]

[0076] [Table 2]

[0077] (2) Evaluation method The initial hardness, hardness after heating, glossiness, and crystal orientation of each of the obtained silver-plated products were evaluated. Each evaluation method will be described below.

[0078] (Initial hardness) The hardness of the silver-plated material was measured by Vickers hardness using a micro Vickers hardness tester ("Micro Vickers Hardness Tester HM-221" manufactured by Mitutoyo Corporation). Here, an indentation was made on the silver-plated material after preparation with a load of 10 gf, a drop time of 3 sec, a hold time of 10 sec, and a rise time of 3 sec, and the Vickers hardness was measured. Then, the Vickers hardness was measured at five arbitrary points on the silver-plated material, and the maximum and minimum values ​​were discarded, and the average of the three points was calculated to determine the Vickers hardness as the hardness in the initial state.

[0079] (Hardness after heating) To measure the hardness after heating, the silver-plated material was heated in air at 100°C for 168 hours in a constant temperature bath and then air-cooled. The Vickers hardness of the heated sample was then measured using the same procedure as for the initial hardness.

[0080] (Glossiness) The gloss of the silver plating layer in the initial state was measured. The gloss of the silver plating layer was measured in a direction parallel to the rolling direction of the material using a densitometer ("Densitometer ND-1" manufactured by Nippon Denshoku Industries Co., Ltd.), and the obtained value was taken as the gloss.

[0081] (Crystal orientation) The crystal orientation of the silver plating layer in the initial state was measured. The crystal orientation of the silver plating layer was evaluated using an X-ray diffraction (XRD) analyzer (Rigaku Corporation's "Fully automatic multipurpose horizontal X-ray diffraction analyzer Smart Lab") with a Cu tube and Kβ filter method. Specifically, first, the X-ray diffraction pattern was obtained by scanning at a scanning speed of 50 deg / min while changing θ from 6 to 120 deg in the scanning range 2θ / θ. From the obtained X-ray diffraction pattern, the X-ray diffraction peak intensities (X-ray diffraction peak intensities) of the {111}, {200}, {220} and {311} planes of the silver plating layer were corrected by dividing them by the relative intensity ratios (relative intensity ratios when measured in powder) listed in JCPDS Card No. 40783 ({111}:{200}:{220}:{311}=100:40:25:26), and the plane orientation of the X-ray diffraction peak with the strongest corrected intensity was evaluated as the crystal orientation direction of the silver plating layer (preferred orientation plane).

[0082] (3) Evaluation results The results of each evaluation method are summarized in Tables 1 and 2 above.

[0083] As shown in Table 2, in Comparative Examples 1 and 2, the concentration of the selenium compound in the silver plating bath was low, with Se / KCN being 0.1% or less, so that the Vickers hardness in the initial state could be made 120 HV or more, but it was confirmed that after heating at 100° C., it was below 120 HV. In other words, it was confirmed that Comparative Examples 1 and 2 could not realize high heat resistance in the silver plating layer.

[0084] On the other hand, in Comparative Examples 3 to 5, although the concentration of the selenium compound was increased compared to Comparative Examples 1 and 2, with Se / KCN exceeding 0.1%, it was confirmed that the surface of the silver plating layer became rough, whitening occurred, and the glossiness was significantly low.

[0085] In addition, in Comparative Example 6, the concentration of the selenium compound was increased further than in the other Comparative Examples, and Se / KCN was set to 0.31%, whereby high hardness was obtained in the initial state and heat resistance at 100°C. However, it was confirmed that significant whitening occurred and the gloss level was further reduced.

[0086] Thus, it was confirmed that in Comparative Examples 1 to 6, a silver-plated product having both high hardness in the initial state, heat resistance at 100° C., and high gloss could not be obtained.

[0087] In contrast, in Examples 1 to 8, as shown in Table 1, a sulfonic acid group-containing polymer was contained in the silver plating bath, and the selenium compound was at a predetermined concentration with Se / KCN exceeding 0.1%, so that, compared with Comparative Examples 1 to 6, high hardness in the initial state and heat resistance at 100°C were realized, and the Vickers hardness both in the initial state and after heating was 120 HV or more, while whitening was suppressed and high gloss was obtained.

[0088] It was also confirmed that the rate of change in hardness before and after heating could be reduced in Examples 1 to 8. Specifically, it was confirmed that the ratio of the Vickers hardness after heating to the Vickers hardness in the initial state could be made 95% or more.

Claims

1. A silver-plated product having a silver plating layer on a substrate, the surface of the substrate is copper or a copper alloy; The silver plating layer contains selenium, The Vickers hardness in the initial state and the Vickers hardness after heating at 100° C. for 168 hours are both 120 HV or more, The gloss of the silver plating layer is 1.0 or more. Silver plated material.

2. The ratio of the Vickers hardness after heating to the Vickers hardness in the initial state is 95% or more. The silver-plated product according to claim 1.

3. The preferred orientation plane of the silver plating layer in an initial state is the {111} plane. The silver-plated product according to claim 1 or 2.

4. A nickel-containing underlayer is provided between the substrate and the silver plating layer. The silver-plated product according to claim 1 or 2.

5. A terminal for electrical contacts, comprising the silver-plated product according to claim 1 or 2.

6. The method includes a step of forming a silver plating layer on a substrate having a copper or copper alloy surface, In the step of forming the silver plating layer, a silver plating bath is used that contains silver cyanide or silver potassium cyanide, a cyanide salt, a selenium compound, and a sulfonic acid group-containing polymer, and the ratio of the concentration of selenium derived from the selenium compound to the concentration of the cyanide salt is more than 0.1%. A manufacturing method for silver-plated products.

7. The selenium concentration derived from the selenium compound is 85 mg / L or more and 200 mg / L or less. The method for producing a silver-plated product according to claim 6.

Citation Information

Patent Citations

  • Silver plated material and method for producing the same

    JP2016204719A

  • Non-cyanide electrolytic pure silver plating film and plating solution

    JP2022018227A

  • Silver plating material and method for producing same

    WO2016157713A1

  • Silver plated material and method for manufacturing the same

    JP2015110833A